Municipal solid waste management of indigenous community in Kampung Kuala Pangsun, Hulu Langat, Selangor / Siti Nur Azlinda Suhada Binti Mohamad Sabri - Mohamad Sabri, Siti Nur Azlinda Suhada (2015)

(untitled)
With the enactment of Solid Waste and Public Cleansing Management (SWPCM) Act, all solid wastes from household and business are subjected to the Act. However, information on municipal solid waste management of rural communities, especially Orang Asli is inadequate due to lack of research studies. The objectives of the study are to measure amount, types and composition of waste generated, to assess current solid waste management practices and the impact towards the environment, to identify the involvement of Majlis Perbandaran Kajang (MPKj) and Jabatan Kemajuan Orang Asli Malaysia (JAKOA), and to propose for better solid waste management practices. Waste collection, estimation and characterization were conducted in Kampung Kuala Pangsun involving 75 houses. Survey was conducted to assess their solid waste management practices and the impact towards the environment. Also, MPKj and JAKOA were interviewed to recognize their involvement. SPSS 20 software program was used for various statistical analyses. The study found that the daily average amount of solid waste generated per household is 0.57 kg, with per capita weight of 0.12 kg. Among the types of waste being generated are kitchen waste, plastic or highdensity polyethylene (HDPE) and box paper. Most of the Orang Asli stores their household waste in plastic bags and choose for open burning to dispose the household wastes. Throughout the study, it was found that their solid waste management practices affect the environment as well as their lives. The study also found that MPKj and JAKOA have indirect and overlapped responsibility in term of providing solid waste management services, education and awareness to the Orang Asli. To improve their solid waste management practices, Orang Asli should be encouraged to store their household waste in plastic bin. Moreover, more communal bins should be provided to prevent open burning and open dumping.